Ankle and Lower Leg Injuries in Professional Baseball Players. Issue 4 (March 2020) - Lucasti, Christopher J.; Dworkin, Myles; Warrender, William J.; Winters, Brian; Cohen, Steven; Ciccotti, Michael; Pedowitz, David
Background: Ankle and lower leg injuries are very common in sports, and numerous studies have discussed their diagnosis and management. Our study differs in that we report lower leg injuries in professional baseball players spanning the 2011-2016 seasons by utilizing a comprehensive injury surveillance system developed by Major League Baseball (MLB). Purpose: To determine the injury characteristics of ankle and lower leg injuries in professional baseball players during the 2011-2016 seasons by utilizing the MLB injury surveillance system. Study Design: Descriptive epidemiology study. Methods: Our study is a descriptive epidemiological evaluation through a retrospective review of injury data from the MLB Health and Injury Tracking System (HITS) since its implementation in 2010. We included any professional baseball player (MLB and Minor League Baseball [MiLB]) who was identified as having an ankle or lower leg injury between January 1, 2011, and February 28, 2017. Results: Over the study period, there were a total of 4756 injuries, of which 763 (16%) occurred in MLB players and 3993 (84%) occurred in MiLB players. The mean number of days missed for all players was 27.8 ± 141.4 days, with a median of 3 days. From 2011 through 2016, it was estimated that there were 414, 912 athlete exposures (AEs) in MLB and 1, 796, 607 AEs in MiLB. Of the 4756 injuries recorded, 550 (12%) took place during the MLB regular season, and 3320 (70%) took place during the MiLB regular season. Injuries in MLB players, however, were 1.7 times more likely to require surgery ( P < .001). Additionally, rates of injury to the lower leg were stratified by position, with infield players experiencing injuries at a 1.6 times greater rate than any other position ( P < .001). Conclusion: In conclusion, this is the only epidemiological study to focus primarily on ankle and lower leg injuries in professional baseball players, utilizing an injury surveillance system developed by MLB.